A Scientific Method for Startups - Felin, Teppo; Gambardella, Alfonso; Novelli, Elena; Zenger, Todd (Journal of Management, 2024)
Recent scholarship has sought to develop a “scientific method” for startups. In this paper we contrast two approaches: lean startup and the theory-based view of startups. The lean startup movement has served an important function in calling for a normative and scientific approach to startups and venture creation. The theory-based view shares this agenda. But there are differences in the underlying theoretical mechanisms and practical prescriptions suggested by each approach. We highlight these differences and their implications for both research and practice. For example, we contrast lean startup’s emphasis on bounded rationality and entrepreneur–customer information asymmetry with the theory-based view’s emphasis on generative rationality and belief asymmetry. The theory-based view focuses on contrarian beliefs, associated problem formulation, and the development of a startup-specific causal logic for experimentation, resource acquisition, and problem solving. The right mix of entrepreneurial actions is contingent and startup-specific—guided by a startup’s unique theory. After pointing out differences between the lean and theory-based view of startups, we discuss opportunities for partial reconciliation, as well as opportunities for empirically comparing perspectives. Overall, we emphasize that a scientific method for startups needs to recognize the importance of contingent, discriminating alignment between entrepreneurial theories and the actions they prescribe (including different types of experimentation and validation, search, and forms of organization).